Maternal Comorbidities with Full-Term Pregnancy Who Gave Birth to Low Birth Weight Babies at Dr. Saiful Anwar Malang General Hospital - I Wayan Agung Indrawan; Obi Candra Kapisa (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Stunting is a challenge for children's growth and development in the future, which has long-term impacts in the form of reduced cognitive abilities, decreased productivity, and increased risk of infection and non-communicable diseases. Low birth weight (LBW) is a major determinant of stunting in Indonesia. Various multidimensional factors contribute to low birth weight, including maternal factors. Material and Methods: Quantitative descriptive research was conducted at Dr. Saiful Anwar general hospital from July 2021 to September 2022. The variables studied were age, education, occupation, parity status, medical history, number of antenatal care controls, height, mother's body mass index, and baby's birth weight. Results: Of the 54 full-term pregnant women, the majority who delivered LBW babies were nulliparous (42.6%), aged 20-35 years during pregnancy (79.6%), had a history of hypertension during pregnancy (25.9%), antenatal care visits 1-5 times (48.1%), high school degree (48.1%), housewives (75.9%), height ranging between 151-160 cm (64.8%), and BMI 18.5 to 25 kg/m 2 (51.9%). Conclusion: Maternal factors that contribute to the birth of LBW babies include low parities, age 20 to 35 years during pregnancy, hypertension in pregnancy, infrequent antenatal care visits, high school degree, work as a housewife, height ranging between 151 -160 cm, and had a normal BMI. The representation of the mother's BMI and educational level in this study differs from that in previous studies.